Consumption Behavior and Willingness to Pay for Fruit Drinks in Bangkok Metropolitan Area - Vorasayan, Jumpol; Sriwachiratorn, Ruttika; Kessuvan, Ajchara (KnE Life Sciences, 2018)
The purpose of this research was to study consumer behaviors, willingness to pay and the factors affecting willingness to pay for ready-to-drink fruit drinks less than 25% with the certified quality assurance system by using contingent valuation method (CVM) for consumers in Bangkok. The results from double-bounded dichotomous choice found that the consumers were willing to pay for fruit drinks less than 25% with GMP certification at 15.22 baht/bottle and 15.58 baht/bottle for fruit drinks less than 25% with HACCP certification. Factors that affected the consumer’s willingness to pay were education, income and attitudes about product that have been certified. Keywords: Contingent Valuation Method; Double-Bounded Dichotomous Choice; Fruit Juice; Willingness to Pay; Quality Control